Aerosol black carbon measurements in Fort Collins, Colorado - Calame, Lorraine, author; Collett, Jeffrey L., Jr., author (Colorado State University. Libraries, 1999)
Aerosol black carbon concentrations were measured in Fort Collins, a small city in northern Colorado. A Magee Scientific aethalometer was used to obtain real time data. In 1997 a gradual build-up in monthly BC concentrations over the late spring and summer was observed to peak in August and then decline. The number of days featuring high concentrations (> 2000 ng/m3 for 30 minutes) was also observed to rise and fall with an August peak. The monthly trends in aerosol black carbon concentrations suggest some seasonality. Observations of aerosol black carbon concentrations made during this study reveal monthly mean concentrations that vary from 487 to 1004 ng/m3. The BC concentration timelines showed there are usually two daily peaks in the data. These peaks usually occur between 0600 - 0800 and 1600 - 2100, hours associated with peak traffic. Concentrations of BC were found to correlate reasonably well with CO concentrations over time scales of up to a week. The covariance in our data set suggests they were emitted from a common set of combustion sources. The results of this study indicate there is little relationship between measured BC concentrations and long range transport patterns, as back-trajectory results indicated that long range transport of air masses from particular regions does not influence whether BC concentrations in Ft. Collins are high or low. The observed BC concentrations tended to decrease with increasing wind speed which is consistent with emissions from a local source that would tend to be diluted at higher wind speeds. On shorter timescales of minutes to hours, the study revealed the importance of individual sources on BC concentrations. Passages of diesel locomotives near the site were shown to increase BC concentrations on many occasions when local winds were favorable to transporting locomotive emissions to the aerosol sample site. The impact of this source, however, was fairly limited in its duration, with concentration spikes typically lasting only about 10 minutes. Train passage also exerted an indirect effect on BC concentrations, perhaps associated with a period of increased BC emissions by vehicles idled at train crossings. Fires were also shown to influence BC concentrations during the study. The large fires associated with the July 1997 flood and smaller fires associated with a CSU student riot were observed to increase BC concentrations. The number of fires during the study period, however, was very low. Impacts of two prescribed bums along the Front Range on Ft. Collins BC concentrations were observed to be fairly minor. Correlation of BC concentrations with "total" particle number concentrations (as measured by a Condensation Nucleus Counter), and number concentrations of particles with diameters greater than 0.3 µm (as measured by a Climet Optical Particle Counter) were extremely weak on long time scales and often weak on time scales as short as a day. This reflected the diverse sources of the aerosols. Some of these were probably primary combustion aerosol (and therefore are likely to correlate with BC), but others were the secondary aerosol fraction of CN or particles larger than 0.3 µm that are not expected to correlate strongly with BC concentrations. BC concentrations were independent of the diurnal pressure patterns, but were affected by synoptic pressure patterns. Frontal passages were marked by low BC concentrations. BC concentrations were not found to be depressed on summer days featuring precipitation, as the duration of summer thunderstorms is typically too short to scavenge enough aerosol particles to significantly influence the daily average BC concentration. In addition, primary aerosol particles that are generated locally by vehicle emissions would be replenished rapidly in the atmosphere following precipitation. Absorption coefficients were derived from the aethalometer and the difference between transmissometer and nephelometer data. The monthly mean values ranged from 0.005 - 0.009 km-' for the aethalometer, and 0.036 - 0.038 km-1 for the transmissometer and nephelometer. The aethalometer derived absorption coefficients are on the order of 10 - 20% of the absorption coefficients determined from the paired nephelometer and transmissometer measurements, and only 6 - 11% of the total extinction measured by the transmissometer.
March 1999.
Also issued as Lorraine Calame's thesis (M.S.) -- Colorado State University, 1999.
Keywords: Aerosols -- Measurement; Carbon-black -- Measurement; Air -- Pollution -- Colorado -- Fort Collins -- Measurement